Coping Stress Ditinjau dari FoMo dan JoMO pada Remaja - Riski Rahmad Ramadhani; Faqihuddin, Adinda Amelia; Faqihuddin, Ahmad (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to examine the relationship between coping with stress, Fear of Missing Out (FoMO), and Joy of Missing Out (JoMO) among adolescents. Using a quantitative correlational approach, the research involved 100 students aged 15–18 years from SMK CORDOVA, selected through simple random sampling. Data were collected using validated Likert-scale instruments measuring FoMO, JoMO, and coping stress. Data analysis included descriptive statistics, Pearson correlation, and multiple regression analysis. Results showed that FoMO and JoMO significantly predict coping stress (R = 0.698, R² = 0.487, p < 0.01), with FoMO exhibiting a negative correlation (r = -0.522, p < 0.01) and JoMO a positive correlation (r = 0.436, p < 0.01) with coping stress. These findings indicate that FoMO has a negative relationship with coping stress, while JoMO has a positive relationship with coping stress. So, it can be concluded that the higher the FoMO in adolescents, the worse it will be in coping with stress. And vice versa, the higher the JoMO, the better the ability to cope with stress.